The drama classroom : action, reflection, transformation - Taylor, Philip, 1959- (RoutledgeFalmer, 2003)
How can teachers incorporate drama into the curriculum? What drama activities are especially successful? How do teachers know when students are learning in, through and about drama? Teachers who are new to drama, or those wishing to refresh their knowledge and ideas, should find practical answers and guidance in this text. The book introduces the work of Cecily O'Neill to demonstrate the entry points to drama lessons, the pre-texts, and how educators need to introduce lessons with challenging material. He then uses the work of David Booth to highlight one aspect of drama - storydrama - and how it can be used as an effective learning medium across the curriculum.